A preliminary study on site selection to host ISME2006 Conference- Kuala Lumpur Convention Center / Noor Badairiah Bakar - Bakar, Noor Badairiah (2005)
In addition to make the selection location looks interesting to host one conference with status an international conference, it must consider many type of factors whether internal or external factors. Other than that, a good selection location must considering the cost of rent the building or location, the level of qualities infrastructure, government and political structure during hosting the conference and economic situation during that time. The suitable site selection in hosting the conference like ISME2006 Conference can give a good reputation towards our country where this conference will participating by overseas delegates which will bring our country name at their home. It is big responsibilities to make sure the selection of right location can give a good impact towards the participation from the people towards ISME2006 Conference. Beside that, the effectiveness of the accommodation services, public transportation, traffic situation and utilities services are other important factors that must be to looks to make the ISME2006 Conference success. A feedback from the respondents towards this study is important to identify and making a corrective action towards the problems that will be exist. So, this study will give many benefits towards the people who are involve whether directly or indirectly in making this conference success. The responds from respondents are according their individual characteristics and values, environmental situation and the location site itself. Hoping from this study will give many tips and reference towards the other parties to make an analysis how to select the suitable location to host conference like International Society for Music Education (ISME2006).